Analisis Metode dan Proses Pengembangan Knowledge Management System: Sebuah Tinjauan Literatur Sistematis - Ursia, Axel Theo Winata; Ugrasena, Anak Agung; Lim, Steven; Farisi, Ahmad (MDP Student Conference, 2025)
Pl The Information System plays a crucial role in managing and optimizing organizational assets to achieve strategic goals. One method used to enhance the effectiveness of information systems is the Knowledge Management System (KMS), which aids in managing resources such as information technology, management, and finance. This study examines KMS using the Systematic Literature Review (SLR) approach on 15 relevant journals. The analysis reveals that knowledge-sharing systems are the most developed KMS process (40%), facilitating the dissemination of explicit and tacit knowledge. The Tiwana framework dominates (53.33%) due to its flexibility and systematic stages, while web-based KMS is the preferred choice (80%) for its accessibility. Additionally, discussion forums are the most advanced feature (66.67%), supporting real-time communication and knowledge archiving. This study highlights the latest trends in KMS development and proposes the integration of artificial intelligence (AI) and machine learning (ML) to enhance its effectiveness.